2008
DOI: 10.1177/0091270008321790
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Efavirenz When Co‐administered With Rifampin in TB/HIV Co‐infected Patients: Pharmacogenetic Effect of CYP2B6 Variation

Abstract: The goal of this study was to determine the effect of CYP2B6 genetic variation on the steady-state pharmacokinetics of efavirenz (600 mg/day) in TB/HIV co-infected patients receiving concomitant rifampin, a potent CYP inducer. In the 26 patients studied, CYP2B6 c.516GG, GT and TT genotype frequencies were 0.27, 0.50 and 0.23, respectively. Mean plasma efavirenz area-under-the-curve was significantly higher in patients with CYP2B6 c.516TT than in those with GT (107 vs. 27.6 μg.h/mL, P < 0.0001), or GG genotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 35 publications
10
33
0
Order By: Relevance
“…Although the CYP2B6 516GϾT SNP is well known to be useful for predicting plasma efavirenz concentrations, little is known about the plasma efavirenz concentration prediction potential of the other two SNPs. Previous studies in Thais (13,17) and members of other ethnic groups (12,15,24) showed high plasma efavirenz concentrations in HIV-infected patients with the CYP2B6 516TT genotype while receiving rifampin. The frequency of this allele ranges from 15% in Asians up to 50% in Africans (11,15,25).…”
Section: Discussionmentioning
confidence: 86%
“…Although the CYP2B6 516GϾT SNP is well known to be useful for predicting plasma efavirenz concentrations, little is known about the plasma efavirenz concentration prediction potential of the other two SNPs. Previous studies in Thais (13,17) and members of other ethnic groups (12,15,24) showed high plasma efavirenz concentrations in HIV-infected patients with the CYP2B6 516TT genotype while receiving rifampin. The frequency of this allele ranges from 15% in Asians up to 50% in Africans (11,15,25).…”
Section: Discussionmentioning
confidence: 86%
“…In one study, the change in efavirenz exposure following coadministration with rifampin ranged from a decrease of 65% to an increase of 37% (21), which suggests interindividual differences in enzyme activity. Furthermore, studies have shown that individuals with CYP2B6 516 TT genotypes are at risk of high efavirenz plasma exposures even in the presence of rifampin (20,29). However, efavirenz trough concentrations, the best predictor of virological activity, have been shown to remain above the concentration necessary to suppress HIV in vitro in patients on concomitant rifampin (22).…”
Section: Discussionmentioning
confidence: 99%
“…Sex is reported to have a modest influence on the pharmacokinetic profiles of certain antiretroviral drugs, including EFV (6,29). A single nucleotide polymorphism at position 516 on the CYP2B6 gene has been widely reported to influence the pharmacokinetics of EFV (3,14,18,19,31,32,33,38,39). India has a large number of HIV-infected individuals, and access to ART is improving.…”
mentioning
confidence: 99%